The structure of anticorrelated networks in the human brain - Martinez-Gutierrez, Endika; Jimenez-Marin, Antonio; Stramaglia, Sebastiano; Cortes, Jesus M. (Frontiers in Network Physiology, 2022)
During the performance of a specific task or at rest, the activity of different brain regions shares statistical dependencies that reflect functional connections. While these relationships have been studied intensely for positively correlated networks, considerably less attention has been paid to negatively correlated networks, a.k.a. anticorrelated networks (ACNs). Here, we have addressed this issue by making use of two neuroimaging datasets: one of N=192 young healthy adults; and another of N=40 subjects that was divided into two groups of young and old participants. We first provided a full description of the anatomical composition of the different ACNs, each of which participated in distinct resting-state networks (RSNs). In terms of their frequency of participation, from highest to the lowest, the major anticorrelated brain areas are the precuneus, the anterior supramarginal gyrus and the central opercular cortex. Subsequently, by evaluating the more detailed structure of ACNs, we show it is possible to find significant differences in these in association with specific conditions, in particular by comparing groups of young and old participants. Our main finding is that of increased anticorrelation for cerebellar interactions in older subjects. Overall, our results give special relevance to ACNs and they suggest they may serve to disentangle unknown alterations in certain conditions, as might occur in neurodegenerative diseases at early onset or in some psychiatric conditions.